2007
DOI: 10.1029/2006sw000295
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of occurrence of large solar energetic particle events prior to 1958 and a possible repetition in the near future

Abstract: It is shown that the >4 GeV fluence of large solar energetic particle events was a factor of 10 greater and the frequency of occurrence a factor of four greater prior to 1958 than during the space era. There were two events in 1946 and 1949 with >4 GeV fluences similar to that of 23 February 1956, suggesting that the >4 GeV fluence of the largest probable event for a similar period would be ∼3 times greater. The historic cosmic ray and glaciological records indicate that the fluences and probability of occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…The three LGLEs occurring after 1958 were much smaller than the earlier 5 LGLEs and occurred during relatively low HMF values. McCracken [2007b] suggested that LGLEs occur preferentially when the HMF is ≤6.5 nT, supporting the earlier results [ McCracken et al , 2004] from the lower‐energy LSEP events.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The three LGLEs occurring after 1958 were much smaller than the earlier 5 LGLEs and occurred during relatively low HMF values. McCracken [2007b] suggested that LGLEs occur preferentially when the HMF is ≤6.5 nT, supporting the earlier results [ McCracken et al , 2004] from the lower‐energy LSEP events.…”
Section: Introductionsupporting
confidence: 87%
“…However, it has long been known [ Cliver et al , 1982; Smart and Shea , 1991] that the first five GLEs, all observed prior to 1958, were far more intense than those that followed. A detailed calibration of the ionization chamber and NM records of two common events [ McCracken , 2007b] has quantified and confirmed that result.…”
Section: Introductionmentioning
confidence: 79%
“…Nor, therefore, is there a simple connection with the corresponding variations in the sunspot number, GCR spectrum and abundance of the 10 Be isotope (figure 8b). We can expect a reversion to the more frequent large SEP events seen just before the space age (McCracken, 2007b). From the inferred fluences of >4 GeV particles, McCracken (2007b) proposes that solar activity must be high enough to give large flares but not so high that the open solar flux is large.…”
Section: Century-scale Variationsmentioning
confidence: 90%
“…Work by McCracken et al (2004) and McCracken (2007b) implies that if Fig. 14 included smaller cycles with SSN cycle values in the range from 0-50, e.g., for the current cycle 24 (Richardson 2013), we might see an anticorrelation between F 200 and SSN cycle .…”
Section: Variation Of High-energy Sep Events With Long-term Solar Actmentioning
confidence: 97%